Effective ways to develop and maintain robust sport-confidence: Strategies advocated by sport psychology consultants - Beaumont, C.; Maynard, I. W.; Butt, J. (Journal of Applied Sport Psychology, 2015)
Based on recent evidence, this study identified 10 strategies advocated by sport psychology consultants as effective at developing and maintaining robust sport-confidence in athletes. Due to the study's exploratory nature, qualitative interviews were conducted and content analyzed. Six themes emerged for developing robust sport-confidence and 4 emerged for maintaining robust sport-confidence. Findings reveal a need to develop an athlete's signature strengths, increase pressure experienced in training, and identify broad stable sources of confidence to develop robust sport-confidence. Consultants reported that maintaining robust sport-confidence occurs through constant development. Theoretical implications and future research directions are discussed.